Reflecting on Early Help with Migrant Families: A View from Practice. Issue 3 (27th May 2022) - Begum, Koyrun; Flint, Tracey; Hunt, Grace; Jolly, Andy; Stringer, Amy
Abstract : This paper describes a practitioner reflection on early help for migrant families with no recourse to public funds. We used Maclean's 'weather model' to examine the positives and challenges of the work. The reflection led to positive changes in programme delivery, but also highlighted tensions between following a structured practice manual and allowing practitioner autonomy, and the friction that 'hostile environment' restrictions caused between statutory and voluntary sectors, and between service users and local authority social workers. We suggest that the experience highlights the need for future service development which includes the voice of social workers.